Nezemědělská povaha životního způsobu spišských Romů: stereotypy a realita - Vojtěch Pelikán (AntropoWebzin)
Opposition to he majority’s agricultural way of life could be – according to some anthropologists (e.g. M. Stewart) – the most fitting interpretative frame for gypsy identity. My contribution tries to find out whether this perspective is appropriate for the context of gypsy settlements in Slovakia. The study is based on field research. It concentrates first on the issue of major stereotypes, where the term “gypsy” represents the most complex image of stranger. Gypsies are considered that way mainly because of the missing connection to land and soil. In the settlements, the study looks for the roots of the relative absence of agricultural patterns. It describes aspects contradicting the major way of life and it tries to show differences between traditionally settled Roma and traveling ones. The text concludes with a discussion about three areas that might have a connection with agriculture: the strategy of solving everyday problems, the relationship to conservation and the dynamic of consumption.